BASIC PRINCIPLES OF ISLAMIC EDUCATION MANAGEMENT - Yuliani, Tri; Annisa, Mella; Gusnita, Fitria; Triana, Mamy (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
The basic principles of Islamic Education Management contain various flexible general principles so that they are in line with good progress and development. These principles are what distinguish between general education management and Islamic education management. The purpose of this study is to explain the basic principles of management in Islamic Education. The research method used is qualitative with a literature study approach. This study was conducted using a number of data and information derived from the results of the literature which were then presented with new results. The results of the study indicate that Islamic Education Management contained in the Al-Quran and its relevance to life in the Industrial Revolution 4.0 Era is the principle of sincerity, honesty, trustworthiness and justice. One of the basic principles that is no less important in Islamic Education Management is the nature of justice in schools, students must be instilled with the values of Islamic education, namely multicultural Islamic education as a basis or foundation that is incorporated in this Islamic Education Management, the theory of justice can be utilized.